Laws of Physics Define the Insignificant Warming of Earth by CO2 - Lightfoot, H. Douglas; Ratzer, Gerald (Journal of Basic & Applied Sciences, 2023)
This study provides temperature estimates about the effect of carbon dioxide (CO2) in warming the Earth’s atmosphere using readily available information. It compares the grams of water vapor per kilogram (kg) of dry air with the number of grams of CO2 per kg of dry air. This comparison is over a year for 20 representative areas of the Earth. It shows the grams of water vapor range from 0.1 to 44.0 times that of CO2. The increased heat content (enthalpy) of the atmosphere by CO2 causes a maximum temperature increase of 0.006oC from the Poles to the Equator. This amount is too small to measure. These quantitative results indicate that the Tropics, representing 39.8% of the Earth’s surface, contain almost three-quarters of the atmosphere’s water vapor. In contrast, the Arctic and Antarctic areas at the Poles have an estimated 0.9% of the atmosphere’s water vapor. Water vapor is the significant greenhouse gas that keeps the Earth from being a frozen planet.